Heme Oxygenase-1 Induction in Human BeWo Trophoblast Cells Decreases Toxoplasma gondii Proliferation in Association With the Upregulation of p38 MAPK Phosphorylation and IL-6 Production - Almeida, Marcos Paulo Oliveira; Mota, Caroline Martins; Mineo, Tiago Wilson Patriarca; Ferro, Eloisa Amália Vieira; Barbosa, Bellisa Freitas; Silva, Neide Maria (Frontiers in Microbiology, 2021)
Heme oxygenase-1 (HO-1) enzyme exerts beneficial effects at the maternal-fetal interface, especially in trophoblasts, being involved in survival and maturation of these cell phenotypes. Trophoblast cells play essential roles throughout pregnancy, being the gateway for pathogens vertically transmitted, such as Toxoplasma gondii. It was previously shown that HO-1 activity was involved in the control of T. gondii infection in vivo, however, its contribution in trophoblast cells during T. gondii infection, remain undefined. Thus, this study aimed to investigate the influence of HO-1 in T. gondii-infected BeWo and HTR-8/SVneo human trophoblast cells. For this purpose trophoblast cells were infected and the HO-1 expression was evaluated. T. gondii-infected BeWo cells were treated with Hemin or CoPPIX, as inducers of HO-1, or with Bilirubin, an end-product of HO-1, and the parasitism was quantified. The involvement of p38 MAPK, a regulator of HO-1, and the cytokines production, were also evaluated. It was found that T. gondii decreased the HO-1 expression in BeWo but not in HTR-8/SVneo cells. When treated with the HO-1 inducers or Bilirubin, BeWo cells reduced the parasite proliferation. T. gondii also decreased the p38 MAPK phosphorylation in BeWo cells, on the other hand, HO-1 induction sustained its activation. Finally, the IL-6 production was upregulated by HO-1 induction in T. gondii-infected cells, which was associated with the control of infection.